Pengaruh Edukasi Nutrisi dengan Audiovisual terhadap Perilaku Pemberian MP-ASI Oleh Ibu dan Pertumbuhan Anak Usia 6-24 Bulan: Systematic Literatur Review - Kurniawati Kurniawati; Tesha Hestyana Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Complementary food for breast milk (MP-ASI) is an additional food that is clean and rich in nutrients and functions for good child growth. Mothers must have good and appropriate behavior in giving MP-ASI to children so that children's growth is optimal. Good and proper feeding behavior requires an education to improve maternal behavior by providing nutrition education with audiovisual media. The aim is to present an overview of the use of audiovisual media in nutrition education on the behavior of giving complementary feeding and the growth of children aged 6-24 months. Literature review through Google Scholar, Science Direct, PMC and Cocherance Library journal in the last 5 years (2015-2020). The data were analyzed in a table containing the author's title, year, methodology, results and recommendations. The results obtained six relevant articles. The six articles explain that nutrition education with audiovisuals does not have a significant difference with other educational media in increasing the behavior of giving complementary feeding by mothers, while for the growth of children the use of audiovisual media education has not been able to fully increase growth. The implementation of audiovisual education by health workers must pay attention to the content and mechanism of information delivery. Good content is short but clear, contains demonstrations and uses easy-to-understand language. The delivery mechanism is provided on an ongoing basis and can be done in collaboration with other media.